Comparison of Parent and Child Ratings of Fruit and Vegetable Liking to Assess Parent Accuracy as Proxy Reporters. Issue 2 (4th March 2019) - Stage, Virginia C.; Downing, Carrie; Hegde, Archana V.; Dev, Dipti A.; Peterson, Amanda D.; Goodell, L. Suzanne
ABSTRACT: This study examined the accuracy of parent-report child fruit/vegetable (FV) liking. Child/parent dyads ( n = 24) were recruited from six Head Start preschools in North Carolina. Liking for 10 FVs was assessed using a validated pictorial tool for children; a similar scale was used for parents. Negative relationships were observed between parent/child for one fruit (grapes) and one vegetable (broccoli). Positive relationships were observed among oranges, grapes, and overall fruit rankings. Parents tended to rank children's liking of fruits higher than their children, while children ranked liking vegetables higher. Findings suggest parents may not be accurate respondents for preschool children's FV liking.